The Effect Of Operational Efficiency On The Financial Performance Of Banks In Indonesia - Ivan Wiryawan; Seno Banyu Aji Yudha Pratama; Henny Setyo Lestari; Farah Margaretha (SEAN Institute, 2024)
This study aims to provide insight into asset utilization, company size, and loan quality significantly affecting the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX). In addition, it can show factors that can strengthen the stability and efficiency of banks which ultimately have an impact on the economy as a whole, especially the community massively. The novelty of this study is the addition of asset utilization variables that are included in the independent variables. The background of this research is driven by the increasing complexity of the banking sector, particularly in Indonesia, where the efficiency and stability of banks play a crucial role in overall economic health. With the rapid growth of the financial sector, especially in the context of banking, it becomes essential to evaluate how effectively these institutions utilize their assets and maintain loan quality in order to optimize financial performance. The research method used by the researcher was quantitative with secondary data sources obtained from 42 banking companies for a 5-year period (2020 - 2023). The data analysis technique used is panel data regression analysis. The results showed that NIITA, NICTA, OEOI, SIZE, and LOAN had a significant impact on financial performance (NIM), and only the CAP variable did not have a significant historical effect. The implications in the research are devoted to financial managers to determine the proper management of assets so that business goals can be obtained, especially in improving investor welfare. The focus of this research is to strengthen the cruciality of ownership structure and liquidity for investors in choosing the right investment opportunities in a banking company.